RESEARCH OF THE SUFFA RADIO OBSERVATORY IN ZOMIN - Hotamov, Jaxongir (Физико-технологического образование, 2023)
Radio Astronomical Observatory of Suffa, and new proposals for radioastroclimatic (seeing) studies for atmospheric radio prediction are described